Pleiotropic Role and Bidirectional Immunomodulation of Innate Lymphoid Cells in Cancer - An, Zhengwen; Flores-Borja, Fabian; Irshad, Sheeba; Deng, Jinhai; Ng, Tony (Frontiers in Immunology, 2020)
Abstract: Innate lymphoid cells (ILCs) are largely tissue-resident and respond rapidly towards the environmental signals from surrounding tissues and other immune cells. The pleiotropic function of ILCs in diverse contexts underpins its importance in the innate arm of immune system in human health and disease. ILCs derive from common lymphoid progenitors but lack adaptive antigen receptors and functionally act as the innate counterpart to T cell subsets. The classification of different subtypes is based on their distinct transcription factor requirement for development as well as signature cytokines they produce. The discovery and subsequent characterisation of ILCs over the past decade has mainly focused on the regulation of inflammation, tissue remodelling and homeostasis, whereas the understanding of the multiple roles and mechanisms of ILCs in cancer is still limited. Emerging evidence of the potent immunomodulatory properties of ILCs in early host defence signifies a major advance in the use of ILCs as promising targets in cancer immunotherapy. In this review, we will decipher the non-exclusive roles of ILCs associated with both pro- and anti-tumor activities. We will also dissect the heterogeneity, plasticity, genetic evidence and dysregulation in different cancer contexts, providing a comprehensive understanding of the complexity and diversity. These will have implications for the therapeutic targeting in cancer.